Economic and Political Risk Aversions to Illicit Financial Flows: A Rethink of the Portfolio Choice Factors - George Ayuune Akeliwira (PanAfrican Journal of Governance and Development, 2023)
The study examines the long-term causal relationship between public debt, governance quality, and illicit financial flows in sub-Saharan Africa. Annual time series data were gathered from the World Bank Governance Indicators, International Monetary Fund Economic Outlook, and Global Financial Integrity from 2005 to 2014. The approach adopted in the study is in the tradition of the portfolio choice framework of tax evasion, rooted in the investment theory of capital flight. The study finds that there is a negative and statistically significant long-run relationship between governance quality and illicit financial flows. The results also show a negative and statistically insignificant relationship between public debt and illicit financial flows. The findings suggest that weak institutional oversight, poor regulatory quality, corruption, and political crises are important determinants of illicit financial outflows in the region. It concludes that governments need to improve the transparency of financial transactions, including the beneficial ownership of corporate structures and tax information. The results also indicate the need to strengthen institutions such as customs, anti-corruption, and other law enforcement agencies to detect intentional trade misinvoicing as tax evaders exploit loopholes in tax administration peculiar to developing countries. The study is timely as resources are critically needed to rebuild economies in view of the global COVID-19 outbreak and its deleterious effects on low-income countries. The study is also relevant for policymakers as it presents pointers to the factors that proliferate illicit capital outflows from the region.